Randomized controlled trial of erdosteine for acute cough in children with colds - Yenny Yenny; Roni Naning; Amalia Setyati (Paediatrica Indonesiana, 2011)
Background T h e prevalence of the common cold in children is high, v.ith 30% of cases exhibiting an acute cough, the most common complaint by parents. Erdosteine, a recently developed cough medicine, is available for children. Erdosteine has been reported to increase mucodliary clearance, act as an antioxidant and prevent bacterial adhesion.